The Impact of Ownership Structure, Moral Hazard and Capital Regulation on Risk Taking in Malaysian Banks - Nora Azureen, Abdul Rahman (2012)
This study examines relationship between ownership structure and moral hazard with risk taking of Malaysian banks and also investigates the moderating effects of capital regulation on these relationships. Despite many claims and arguments that associate high risk taking of Malaysian banks with the existence of large shareholders and moral hazard related to loan activities (high loan growth and loan concentration), the practices are still prevailing until present. The fact that banks are highly regulated also creates issue on how regulation moderates the relationship between ownership structure and moral hazard related to loans with bank risk taking. Bank risk taking in this study is measured by standard deviation of return on equity, standard deviation of return on assets and Z-SCORE (insolvency risk). Ownership structure comprised of insider ownership, family ownership, government ownership, institutional ownership and foreign ownership. Moral hazard is proxied by loan growth and loan concentration while capital regulation is proxied by capital adequacy requirement. Using secondary data, total number of observations of this study is 294. Data are collected from 21 commercial banks in Malaysia, comprising of 9 domestic banks and 12 foreign banks over 1990-2008 period. In testing the relationships between ownership structure, moral hazard and capital regulation on bank risk taking, two regression test are used. Multiple regression is used to test the relationship between ownership structure and moral hazard on bank risk taking, while hierarchical moderated multiple regression is used to test the moderating effects of capital regulation on the relationship between ownership structure and moral hazard to bank risk taking. The multiple regression results revealed that different type of ownership structure has different impact on bank risk taking. The results on moral hazard show that loan growth increased insolvency risks of banks, while loan concentration create variation in bank returns (standard deviation of return on equity) but decrease probability of failure (high Z-SCORE) of the banks. Further, hierarchical moderated multiple regression revealed that capital adequacy requirement has significant moderating impact on the relationship between ownership structure and moral hazard with standard deviation of return on equity and insolvency risks. In contrast, it has insignificant moderating effects on the relationship between ownership structures and moral hazard with standard deviation of return on assets. Overall, findings of this study imply that the existence of large shareholders in Malaysian banks does not increase bank risk taking (as measured by variations of returns and insolvency risks), the impact of loan growth in increasing banks risks will only be felt in the long term while loan concentration, although create variation in bank return but would increase bank stability in the long term. The result also imply that capital regulation implemented by Malaysian regulators is appropriate for the Malaysian banks as higher capital adequacy requirements might creates unintended effects whereby banks might response by increasing their risk taking.